Association of gut dysbiosis with intestinal metabolites in response to antibiotic treatment. (March 2019) - Khan, Tariq Jamal; Hasan, Mohammed Nihal; Azhar, Esam I.; Yasir, Muhammad
Abstract: Gut microbiota (GM) is associated with metabolism, provides energy-harvesting efficiency and protection against opportunistic pathogens through competitive exclusion to the host. Previous studies highlighted the temporary as well as permanent alteration to GM resulting from different antibiotics treatment. The diverse class of antibiotics may damage the metabolic homeostasis and can alter the level of intestinal metabolites [including amino acids, bile acids (BAs), glucose, short chain fatty acids (SCFAs)] through alteration in abundance of metabolically active bacteria. The antibiotics administration causes the disturbed profile of related microbial metabolites, especially that of BAs, primary and secondary BAs (conjugated or unconjugated BAs). The antibiotics intake causes the reduced bacterial diversity that makes the individuals susceptible towards diseases. To a large extent, we tried to clarify the adverse effects of classes of antibiotics on the GM composition, and the consequent impacts of dysbiosis on the BAs feedback loop between liver and gut, which involves the farnesoid-X-receptor-fibroblast growth factor (FXR-FGF) pathway. The current review discusses the antibiotics-GM-BAs nexus during Clostridium difficile infection (CDI) and the recommended therapy includes faecal microbial transplant (FMT) in countering the exposure of harmful antibiotic and bacteriotherapy as an alternative therapeutic intervention in treating the recurrent CDI.